1993
DOI: 10.1016/s0022-5347(17)36197-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Bacillus Calmette-Guerin Immunoprophylaxis of Superficial Bladder Cancer: Results of a Controlled Prospective Trial with Modified Treatment Schedule

Abstract: A controlled prospective trial on 94 patients evaluated the efficacy of intravesical Pasteur strain bacillus Calmette-Guerin (BCG) administration as prophylaxis against tumor recurrences after complete endoscopic resection of superficial bladder cancer. The treatment schedule, consisting of an initial 6-week course of instillations and a single quarterly maintenance dose to the responders, was modified to those of the latter who were at high risk for recurrence and who received an additional separate 4-week co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…Contrary to well-differentiated (G1) bladder tumour cell lines, poorly differentiated (G3) cell lines exhibit significant internalisation of BCG (Bevers et al, 1998). Clinically, these data relate well to observations that show a better response to BCG treatment of high-grade compared to low-grade tumours (Table 1) (Melekos et al, 1993).…”
Section: Internalisation Of Bcg and Phenotypical Alterations Of Urothsupporting
confidence: 85%
See 1 more Smart Citation
“…Contrary to well-differentiated (G1) bladder tumour cell lines, poorly differentiated (G3) cell lines exhibit significant internalisation of BCG (Bevers et al, 1998). Clinically, these data relate well to observations that show a better response to BCG treatment of high-grade compared to low-grade tumours (Table 1) (Melekos et al, 1993).…”
Section: Internalisation Of Bcg and Phenotypical Alterations Of Urothsupporting
confidence: 85%
“…In these patients, the benefits of treatment outweigh the burden of side effects. Moreover, BCG seems to exert a better antitumour effect in CIS and high-grade cancer (Melekos et al, 1993;Kurth et al, 2000).…”
mentioning
confidence: 99%
“…Six controlled trials carried out from 1985 to 1996 showed that BCG decreases recurrence rates from 67% to 29%. [72][73][74][75][76][77][78] Six meta-analyses compared BCG with intravesical chemotherapy; all of them except 1 metaanalysis 79 showed superiority of BCG over chemotherapy in terms of decreasing recurrence. [79][80][81][82][83][84] The effect of BCG on tumour progression has been investigated by Herr and colleagues in 3 randomized trials, each of which demonstrated a significant reduction in disease progression to muscle invasion or metastasis.…”
Section: Efficacymentioning
confidence: 99%
“…In several early larger series, tumor recurrence after transurethral resection of bladder cancer was reduced by 20–65%, with an average of approximately 40% [24,25]. The efficacy of BCG after transurethral resection of bladder cancer for high-risk papillary urothelial carcinoma has been demonstrated in several series of T1 lesions, with recurrence rates of 16–40% and progression rates of 4.4–40%, a substantial improvement compared with TURB alone [26,27].…”
Section: Discussionmentioning
confidence: 99%